Aramaic A History of the First World Language - Gzella, Holger 1974-; Suchard, Benjamin 1988- (Chicago Wm. B. Eerdmans Publishing Co., 2021)
Intro -- Title Page -- Copyright -- Contents -- Preface -- List of Abbreviations and Symbols -- 1. Introduction -- The Importance of Aramaic -- A Brief History of Aramaic Studies -- Hallmarks of Aramaic Grammar -- The Evolution of Aramaic and Its Periodization -- Overview of This Book and a Guide to Further Study -- 2. The Oldest Aramaic and Its Cultural Context -- The Origin of Aramaic and the Linguistic Context of Syria-Palestine -- A New Writing Culture: The Alphabet's Big Break -- Speaking through Stone: The Context of the Old Aramaic Inscriptions -- The Arameans and Their Southern Neighbors: Aramaic Writing Culture in Palestine -- Aramaic on the Move -- 3. Aramaic as a World Language -- Aramaic in Its Imperial Context -- Aramaic as the New Administrative Language of the Assyrian Empire -- Continuity in the Babylonian Period -- Codification and Maximal Extent in the Achaemenid Period -- The Imperial Aramaic Writing Tradition -- 4. Aramaic in the Bible and Early Judaism -- Aramaic's Integration in Palestine -- The Hebrew Bible and Aramaic -- Aramaic Books of the Bible and Their Background -- The Aramaic Literary Tradition of Palestine and the Dead Sea Scrolls -- Aramaic as the Language of Jesus and the Background of the New Testament -- 5. Aramaic Between the Classical and Parthian Worlds -- A Network of Local Aramaic Written Languages -- Palmyra and the Palmyrenes between East and West -- In the Shadow of the Parthian Empire: Hatra, Eastern Mesopotamia, and Babylonia -- Dura Europos: Aramaic in a Greek Administrative Context -- The Arsacid Aramaic Writing Culture of the Parthians -- 6. Syriac and the End of Paganism -- Syriac Christianity and Its Cultural Context in Late Antiquity -- Edessa, the Cradle of Syriac -- The Rise of Christian Syriac Literature in Edessa and Beyond -- Syriac as an International Ecclesiastical Language.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books